NATURE OF MIXED-LAYER CLAYS AND MECHANISMS OF THEIR FORMATION AND ALTERATION - Środoń J. (My University, 1999)
Mixed-layer clay minerals are intermediate products of reactions involving pure end-member clays. They come from natural environments ranging from surface to low-grade metamorphic and hydrothermal conditions. Most often mixed layering is essentially two component, but more complicated interstratifications have also been documented. Variable tendency to form regular 1:1 interstratifications has been observed and explanations of this phenomenon have been proposed. Mixed-layer clays are either di- or trioctahedral; di/trioctahedral interstratifications are rare. Most mixed-layer clays contain smectite or vermiculte as a swelling component. Exceptions are all trioctahedral: serpentine/chlorite in low-temperature environments, and mica/chlorite and talc/chlorite at high temperatures. Solid state transformation and dissolution/crystallization are the two mechanisms responsible for the formation of different mixed-layer clays. In general, the weathering reactions that produce mixed layering are reversals of the corresponding high-temperature reactions, but the reaction paths are quite different. Weathering reactions alter smectite into kaolinite via mixed-layer kaolinite/smectite. Illite, chlorite, and micas react into mixed-layer clays involving vermiculite layer, then into vermiculite, and finally smectite. Interstratifications of smectite and glauconite, serpentine and chlorite, and smectite and talc are characteristic of early diagenesis and indicative of sedimentary environments. Three reactions involving mixed-layer clays—smectite to illite, smectite to chlorite, and serpentine/chlorite to chlorite—proceed gradually during burial diagenesis and are used for reconstructing maximum burial conditions, illite/smectite being the most useful tool. Rectorite, tosudite, talc/chlorite, and mica/chlorite are mixed-layer minerals indicative of temperatures higher than diagenetic, characteristic of low-temperature metamorphism or hydrothermal alteration.